14.4k views
0 votes
3-5g=33 need help with the problem

User Lukk
by
4.6k points

2 Answers

3 votes

Explanation: Start by Isolating the Variable.

-5g=33-3

-5g=30

g=-6 is what makes this true. let's check:

3-5(-6)=33

3+30=33

33=33

hence -6 is the solution.

User Jaho
by
4.3k points
2 votes


\huge\text{Hey there!}



\mathsf{3 - 5g = 33}


\mathsf{-5g + 3 = 33}


\large\text{Subtract by 3 to both sides:}


\mathsf{-5g + 3 - 3 = 33 - 3}


\large\text{Simplify it:}


\mathsf{-5g = 33 - 3}


\mathsf{-5g = 30}


\large\text{Divide -5 to both sides:}


\mathsf{(-5g)/(-5) = (30)/(-5)}


\large\text{Simplify it:}


\mathsf{g = (30)/(-5)}}


\mathsf{g = -6}


\huge\text{Therefore, your answer should be: \boxed{\mathsf{g = -6}}}\huge\checkmark



\huge\text{Good luck on your assignment \& enjoy your day!}


~
\frak{Amphitrite1040:)}

User Bodangly
by
5.3k points